The social cost of carbon falling on the wealthy - Stefan Gössling; Andreas Humpe (Cleaner Production Letters)
Under the Paris Agreement, the responsibility for reducing greenhouse gas emissions lies with individual countries, which submit pledges to the United Nations Framework Convention on Climate Change (UNFCCC) outlining their ambitions and timelines for emission reductions. Within countries, emissions are unevenly distributed among individuals, with the wealthy known to emit disproportionately more. Since greenhouse gas emissions represent a social cost, this paper investigates the economic implications of the lifestyles of the wealthy. The social cost of carbon (SCC) attributed to millionaires—defined based on their assets, including property—is calculated using national emissions data, distributional data, and SCC assessments for both historical (1990–2022) and future periods (2023–2050). The results suggest that only 1.3% of the global SCC, estimated at US$8.7 trillion, was covered by any form of carbon pricing in 2022. Of this amount, 16.5% (US$1.4 trillion) is attributable to millionaires, who represent just 0.8% of the world's population. The most cost-effective climate policy would be to internalize the SCC, ensuring that the carbon price is equal to the SCC. If the SCC remains externalized, the wealthiest individuals could benefit by an estimated US$25.1 trillion over the period from 2023 to 2050. Other market-based mechanisms will be necessary to curb the carbon-intensive consumption patterns of the wealthy.